2022
DOI: 10.1186/s13052-022-01229-2
|View full text |Cite
|
Sign up to set email alerts
|

Manifesto of the pediatricians of Emilia-Romagna region, Italy, in favor of vaccination against COVID in children 5–11 years old

Abstract: Background Following the authorization by the regulatory authorities of vaccination against COVID for children aged between 5 and 11, in Emilia-Romagna Region, Italy, the pediatricians of the Italian Society of Pediatrics (SIP), the Italian Society of Neonatology (SIN), the Cultural Association of Pediatrics, the Italian Federation of Pediatricians (FIMP) and the Italian Union of Family Pediatricians (SIMPeF), who work in the hospital and in the territorial setting, have made a univocal and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Vaccination is the best strategy to reduce the severity of the disease and limit complications of COVID-19. It has been shown that BNT162b2 vaccination can consistently reduce Omicron-associated hospitalizations in children ( 28 , 41 ) and prevent or reduce the associated complications, such as MIS-C ( 42 ), long COVID ( 43 ), and impairment of social and mental wellbeing ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaccination is the best strategy to reduce the severity of the disease and limit complications of COVID-19. It has been shown that BNT162b2 vaccination can consistently reduce Omicron-associated hospitalizations in children ( 28 , 41 ) and prevent or reduce the associated complications, such as MIS-C ( 42 ), long COVID ( 43 ), and impairment of social and mental wellbeing ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study offer new insights into the humoral and cellular response to SARS-CoV-2 mRNA vaccines in children, useful to support public health decisions on the definition of future vaccination strategies in the pediatric age. Improving knowledge on immune response following vaccination may also help overcome vaccine hesitancy, considering that children, as adults, have the right to be protected from severe disease and COVID-19 complications and sequelae ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers agree on the key role of vaccination to prevent Sars Cov2 infection and, most of all, severe disease. According to The manifesto of Pediatricians of Emilia-Romagna region vaccines against COVID are the most effective and safe tool to contrast COVID 19 and for this reason should be considered as a right of children to protect themselves [ 57 ]. Vaccine product-related reactions are seldom reported such as Henoch-Schoenlein purpura reported in an adolescent by Casini et al [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, parents’ willingness to vaccinate their children against COVID-19 has always turned out to be rather low, even lower than their willingness to be vaccinated themselves. In Italy, the intention to accept a COVID-19 vaccine of parents of children <18 years of age was 60.4%, compared to values of 64.5% and 84.1% found in the general population [ 28 , 29 , 30 ]. Detailed knowledge of parental willingness and hesitancy toward pediatric COVID-19 immunization is essential to understand the reasons for non-vaccination and to prepare adequate measures to improve vaccination coverage.…”
Section: Introductionmentioning
confidence: 82%